2004
DOI: 10.1038/sj.onc.1207466
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic inhibition of the JAK-STAT pathway

Abstract: The Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway is an essential cascade for mediating normal functions of different cytokines in the development of the hematopoietic and immune systems. Chronic exposure to arsenic has been found to cause immunotoxicity and has been associated with the suppression of hematopoiesis (anemia and leukopenia). Here, we report the novel finding of arsenic-mediated inactivation of the JAK-STAT signaling pathway by its direct interaction with JAK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…To date, the focus has been on PML and PML-retinoic acid receptor ␣ as major targets of ATO (70). On the other hand, arsenic has been reported to modulate other cell-signaling pathways, especially stress-responsive transcription factors, such as nuclear factor B (NF-B), activator protein 1 (AP-1), and STAT3 (12,37,38,62). Therefore, we examined the involvement of several stress-responsive pathways in the anti-HCV activity of ATO by luciferase-based reporter assays or Western blot analysis using an antibody which specifically recognizes STAT3 phosphorylated at tyrosine 705.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the focus has been on PML and PML-retinoic acid receptor ␣ as major targets of ATO (70). On the other hand, arsenic has been reported to modulate other cell-signaling pathways, especially stress-responsive transcription factors, such as nuclear factor B (NF-B), activator protein 1 (AP-1), and STAT3 (12,37,38,62). Therefore, we examined the involvement of several stress-responsive pathways in the anti-HCV activity of ATO by luciferase-based reporter assays or Western blot analysis using an antibody which specifically recognizes STAT3 phosphorylated at tyrosine 705.…”
Section: Resultsmentioning
confidence: 99%
“…5C and D), suggesting that the AP-1 pathway is also not involved in the anti-HCV activity of ATO. Regarding the STAT3 signaling pathway, ATO has been reported to inhibit the phosphorylation of the STAT3 tyrosine at 705, leading to inactivation of the JAK-STAT signaling pathway (12,62). In contrast, it has been reported that HCV constitutively phosphorylates and activates STAT3 (49,59,67).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher doses of arsenite (>10 μM), strong necrosis starts to substitute apoptosis of cancer cells, diminishing usefulness of this treatment. Two critical enzyme targets, which are suppressed by arsenite treatment, are IKKβ [41] and JAK2 [58]. Inhibition of these enzymes results in a suppression of the NF-κB and STAT3-mediated signaling, which downregulates gene expression of cFLIP, XIAP, cIAP, BclxL [2,59], proteins involved in the regulation of anti-apoptotic protection in the cell (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A small epidemiologic study among a Mexican population exposed to arsenic-contaminated drinking water observed that chronic arsenic exposure increased certain enzyme activity in the heme biosynthesis pathway, although the biological significance of this alteration is not known (14). Arsenite can inactive the Janus-activated kinase/signal transducers and activators of transcription pathway, which plays a critical role in the function of hematopoietic cells, cell proliferation, and differentiation (43). Arsenic-contaminated drinking water has been associated with increased microvascular disease (44) and deficits of capillary blood flow and permeability in clinically normal skin of patients with chronic arsenical poisoning (45).…”
Section: Discussionmentioning
confidence: 99%